Guiding the Differentiation Direction of Pancreatic Islet-Derived Stem Cells by Glycated Collagen - Gokhan Duruksu; Aysegul Aciksari (Stem Cells International)
The microenvironment is an important factor of stem cells regulating their maintenance, survival, and differentiation. The glycation of proteins with reducing sugars through nonenzymatic reactions induces the collagen cross-linking, which causes tissue stiffening, which is enhanced during aging and diabetes. In this study, we aimed to analyze the effect of glycated collagen on the stem cell culture and differentiation. The collagen type 1 was modified by glycation with mannose, rhamnose, arabinose, and glucose. After the culture of mesenchymal stem cells on the coated surfaces with glycated collagen, the differences in cell adhesion, proliferation, and differentiation were compared. The results showed that the modifications did not induce apoptosis or cause cell death. However, the culture of cells on modified collagens improved the proliferation. It was found that the mannose-modified collagen stimulated the adipogenic differentiation of stem cells, and rhamnose-modified collagen supports the differentiation into both osteogenic and insulin-producing cells. The low concentration of monosaccharides during glycation process improved the characteristics of the matrix protein in favor of stem cell differentiation. Modification of the collagen by glycation might be used as a tool to improve natural polymers for material-induced stem cell differentiation in the future.